The method of transitional processes in studies of geological media with magnetic viscosity - N. O. Kozhevnikov; E. Yu. Antonov; G. G. Matasova; Ya. K. Kamnev (Геофизический журнал, 2012)
The paper discusses the effect of magnetically viscous geological materials on the TEM response. Magnetic viscosity is a property of ferromagnetism. In rocks and soils it is often associated with superparamagnetism, or magnetic relaxation of ultra-fine ferrimagnetic mineral grains. Magnetic viscosity in TEM data shows itself as voltage decaying inversely proportional to the first power of time. Most often it is treated as a geologic noise that hinders inversion of TEM response in terms of electrical conductivity. On the other hand, there is evidence that magnetic viscosity effects are related to the mineralogy and history of natural and man-made geological materials. Therefore, it appears reasonable to learn how, (1) using TEM systems of different geometry, to amplify or depress the magnetic viscosity response and (2) interpret it in terms of rock magnetism. We show, through forward calculation of TEM responses, laboratory magnetic viscosity measurements both in time and frequency domains, and inversion of the field TEM data in terms of time-dependant magnetic susceptibility, how magnetic viscosity effects can be used as a source of important information on the near-surface geology. The discussed results present a first experience in applying the TEM method to purposeful investigation into magnetic relaxation of rocks. There are still a number of important issues that remain beyond this consideration and will be a subject of a special study, namely, equivalence, resolution, and influence of measurement errors on the inversion quality.